Morphology and phylogeny of Microdochium chuxiongense sp. nov., a fungus from Southwest China - Tang, De-Xiang; Zou, Wei-Qiu; Wang, Yao-Ming; Huang, Ou; Yu, Hong (Phytotaxa, 2022)
Microdochium includes important plant pathogens, parasitic in economically important wheat, barley, rice and corn, causing economic losses. A new species, Microdochium chuxiongense, was isolated from the host Bondarzewia sp. and reported from China. It was characterized by mycelium immersed and superficial and branched. Conidiophores were cylindrical, borne from the hyphae. Conidiogenous cells were sparse, hyaline, solitary, occasionally curved or swollen. Conidia were single or multiple, long oval, shuttle or sickle, straight or curved, and 0(–3)-septate. Chlamydospores were produced directly from mycelium, single, round or palmate. It was well-supported based on morphological characters and molecular evidence (LSU, ITS, tub2 and rpb2), and was a distinct species within the genus Microdochium. This work increases our understanding of the distribution and host diversity in this group, and provides important taxonomic data to further explore evolutionary relationships in the species of Microdochium.